Individual as Actor Model Based on Edu-eDi YouTube Animation: Short Story Writing Skills - Suprayetno, Edy (IJORER : International Journal of Recent Educational Research, 2026)
This study aims to describe the development of an individual-as-actor model based on Edu-eDi YouTube animation in short story writing instruction. This study was motivated by students' low interest in the learning model used in short story writing activities. The method used was development research or design research with three stages, namely preliminary research, the prototyping phase, and the assessment phase. The developed product was tested in terms of validity, practicality, and effectiveness. Data collection techniques included interviews, observations, questionnaires, tests, and literature review. Validity and practicality data were analyzed through expert review, one-to-one evaluation, and small-group evaluation, while effectiveness was analyzed using normality tests, homogeneity tests, and a one-tailed t-test. The results show that the individual-as-actor model assisted by Edu-eDi YouTube animation meets the criteria of being valid, practical, and effective for implementation in school learning. These findings indicate that the model can support the improvement of students' story-writing skills.